Pattern of Microorganisms of Urinary Tract Infection (UTI) and its Outcomes in Diabetic Patients of Tertiary Intensive Care Unit (ICU) - Kishore, Nand; Khanduri, Sushant; Kakati, Barnali (Academia Anesthesiologica International, 2021)
Background: To assess pattern of microorganism of urinary tract infection (UTI) & its outcomes in diabetic patients admitted in intensive care unit (ICU). Subjects & Methods: One hundred twenty type II diabetes patients admitted in intensive care unit (ICU) of Himalayan Institute of Medical Sciences, Dehradun, Uttarakhand comprising of 78 males and 42 females were studied for UTI. Results: 70 patients had UTI. It was seen in 50 (71.4%) catheterized and 20 (28.6%) non- catheterized, 22 (31.4%) controlled diabetics and 48 (68.6%) uncontrolled diabetics and 38 (54.2%) on insulin and 32 (45.8%) on OHA. Most common gram- negative organism seen in UTI was E coli seen in 42%, gram positive organism was Staphylococcus sciuri in 7% and yeast was Candida albicans in 1% and Candida glabrata in 1.3%. Septic shock occurred in 18 (25%), re- infection in 7 (10%) and death in 4 (5.7%) patients Conclusion: Most commonly occurring gram negative pathogens among diabetic ICU patients was E coli and gram- positive pathogen was Staphylococcus sciuri. UTI was commonly seen among catheterized, uncontrolled diabetics.